Equivalent expressions are two or more expressions that may be made of different terms and numbers but produce the same results regardless of what the value of the variable is. In other words, for every number you sub into the variable (can be x or a or h) spot, both expressions give the same value.

Expand and simplify the expressions and then show that the original version and the simplified versions are equivalent for two variables of x (you choose any values of x).

4(3x + 2) - 5

Firstly, look at the expression and see what we can expand, we expand 4(3x + 2) on its own using our methods from lesson 3,

(Remember the Distributive Property, a(b+c) = ab +bc )

4(3x) + 4(2) =

(4)(3)x + 4(2) =

12x + 8, now we put this back in to our original expression,

4(3x + 2) - 5 =

[ 4(3x + 2) = 12x + 8 ]

12x + 8 - 5 =

12x + 3,

Now we have the original term 4(3x + 2) - 5 and the simplified term 12x + 3, we have to show they are equivalent,

Remember, Equivalent definition : Two or more expressions that have equal results for the same value of the variable (variable in this case is x).

All we have to do is pick ANY two numbers for x, you can pick any, but let's go for 1 and 3,

First, we lets sub x = 1 into both expressions,

4(3x + 2) - 5

4(3(1) + 2) - 5 =

We will gradually start to combine steps of order of operations and the three definitions of properties for speed's sake.

4(5) - 5 =

20 - 5 = 15

Now the other expression,

12x + 3 =

12(1) + 3 = 15

So they are the same for x = 1. Let's check x = 3,

4(3x + 2) - 5

4(3(3) + 2) - 5 =

4(9 + 2) - 5 =

39

12x + 3

12(3) + 3 =

36 + 3 = 39

So, for both expressions we had the same results for the two different values of x. The work we did to simplify the original expression was proof in itself that the original and simplified versions were equivalent, subbing in different values of x just checks us that we were right.

When simplifying an expression, you can check that you simplified it correctly by trying subbing a value into the variable for the original expression from a question and simplified version that you worked out!

A “fun” exercise, try subbing in a massive or obscure number into the two expressions we just worked with (you can use a calculator for this one) and see what happens! They will still be equivalent! Try something like x = 3,456 or x = (147/16)

{5(3x + 3) - 3}/3 - 7

This expression can look quite daunting, but as always, all we have to do is remember our rules and methods. The order of operations, and the three properties (associative, commutative and distributive).

It might help to think of this as “something being divided by 3 then minus 7”,

As order of operations tells us (BEDMAS), deal with the division first,

let’s split this up from the original expression,

{5(3x + 3) - 3}/3,

Now, lets deal with the numerator first,

5(3x + 3) - 3

Expand out our brackets,

5(3x) + 5(3) - 3 =

15x + 15 - 3 =

15x + 12 is our numerator, so we have,

{15x + 12}/3,

Distributive Property,

(15x)/3 + (12)/3 =

5x + 4,

Important to remember to sub this all back into the original expression, so

({5(3x + 3) - 3}/3 = 5x +4)

{5(3x + 3) - 3}/3 - 7 =

5x + 4 - 7 = 5x - 3,

Now we have our simplified version, let's check they are equivalent by subbing in two value of x, let’s try 2 and 4,

Working through this we will start to assume there is an understand about some of the steps of the order of operations and the three properties, however, if you're unsure, never hesitate to work through every step yourself,

x = 2

{5(3x + 3) - 3}/3 - 7

{5(3(2) + 3) - 3}/3 - 7 =

{5(9) - 3}/3 - 7 =

{45 - 3}/3 - 7 =

{42}/3 - 7 =

14 - 7 = 7

5x - 3

5(2) - 3 =

10 - 3 = 7

So, we are right for x = 2, let's check x = 4

x = 4

{5(3x + 3) - 3}/3 - 7

{5(3(4) + 3) - 3}/3 - 7 =

{5(12 + 3) - 3}/3 - 7 =

{5(15) - 3}/3 - 7 =

{75 - 3}/3 - 7 =

72/3 - 7 =

24 - 7 = 17

5x - 3

5(4) - 3 =

20 - 3 = 17

Bingo! 17 = 17